Effect of MCSQ and COSE on service recovery and its impact on customer satisfaction - Rusandy, Deby Santyo; Astuti, Widji; Firdiansjah, Achmad (International Research Journal of Management, IT & Social Sciences, 2018)
This study aims to analyze the influence of MCSQ and COSE on service recovery; analyze the influence of MCSQ and COSE on customer satisfaction; analyze the effect of service recovery on customer satisfaction, and analyze the influence of MCSQ and COSE on customer satisfaction through service recovery. This research uses a quantitative method with a probabilistic character using structural equation modeling analysis. MCSQ and COSE affect service recovery. MCSQ and COSE affect customer satisfaction. Service recovery affects customer satisfaction. MCSQ and COSE affect customer satisfaction through service recovery. Service recovery mediates the influence of MCSQ and COSE on customer satisfaction.